A note on q-truncated exponential polynomials - Raza, N.; Fadel, M.; Cesarano, C. (Carpathian Mathematical Publications, 2024)
In this paper, we introduce the q-truncated exponential polynomials by means of the integral form. Certain properties of the q-truncated exponential polynomials like series definition, recurrence relations, q-differential equations and integral representations are obtained. Also, we introduce the associated q-truncated exponential polynomials, higher order q-truncated exponential polynomials and higher order associated q-truncated exponential polynomials. Furthermore, we obtain their integral forms, generating functions, series definitions, summation and operational formulas.